Regarding the teaching of the subject «Higher Mathematics» at technical universities (MMIT Proceedings, 2024)
The work reflects innovative methods in teaching higher mathematics, their content. In particular, it provides historical data on mathematicians who made a huge contribution to the development of this science and their impact on the evolutionary process of mankind.